Exploring land cover dynamics: open mining activities footprint in Central Bangka District, Indonesia - Winata, Dudy Gilang; Mulyanto, Budi; Suryaningtyas, Dyah Tjahyandari (Journal of Degraded and Mining Lands Management, 2025)
Land cover changes resulting from mining activities in Central Bangka District have often led to environmental degradation, significant challenges for local communities, and disruptions to spatial utilization. This study aims to identify land cover change patterns within the tin mining business license (IUP) area from 2014 to 2022 and evaluate their impacts on ecosystems and land use. The study employed the Maximum Likelihood Classification (MLC) method for satellite image analysis to detect land cover changes. The results indicated that mining land expanded by 2,117.29 ha between 2018 and 2022, primarily due to the conversion of secondary and natural vegetation. Meanwhile, secondary vegetation declined significantly, with 4,187.46 ha reduction from 2014 to 2022, highlighting the extensive exploitation of land for mining activities. Additionally, an increase in water bodies was observed due to the formation of water-filled mine voids, locally known as "kolong". The classification accuracy assessment demonstrated high reliability, with Kappa coefficients of 93.7% in 2014, 92.73% in 2018, and 94.5% in 2022, confirming the effectiveness of the MLC method in detecting land cover changes. The findings of this study provide critical insights for post-mining land management, emphasizing the need for enhanced reclamation and revegetation strategies. A more comprehensive understanding of land change dynamics is expected to support sustainable spatial planning and inform environmental impact mitigation policies in Central Bangka District.